Rational design and electron transfer kinetics of MoS2/CdS nanodots-on-nanorods for efficient visible-light-driven hydrogen generation. (October 2016) - Yin, Xing-Liang; He, Gui-Ying; Sun, Bing; Jiang, Wen-Jie; Xue, Ding-Jiang; Xia, An-Dong; Wan, Li-Jun; Hu, Jin-Song
Abstract: The efficiency of CdS-based photocatalysts for H2 evolution is limited by the ultrafast charge recombination. Here, we demonstrated the one-pot synthesis of a novel MoS2 /CdS photocatalyst with the structure of partially crystalline MoS2 nanodots growing on single-crystalline CdS nanorods. This heterostructure not only effectively reduces the bulk and surface charge recombination owing to single-crystalline CdS nanorod matrix and efficient electron transfer, also provides plenty of active sites for hydrogen evolution reaction (HER) and accessible room for prompt hole extraction. The femtosecond transient absorption (TA) analysis reveals the effective electron transfer from CdS to MoS2 in ~20 ps. As a result, MoS2 /CdS exhibits extraordinary photocatalytic activity with a H2 evolution rate of 60.28 mmol/g/h under visible light irradiation, far exceeding all previous HER photocatalysts with MoS2 as cocatalysts. Graphical abstract: MoS2 /CdS nanodots-on-nanorods was rationally designed and prepared by a facile one-pot solvothermal method. Benefited from the unique nanostructure, this MoS2 /CdS heterostructure exhibits a superior photocatalytic performance for hydrogen evolution. Highlights: Novel MoS2 /CdS nanodots-on-nanorods heterostructures were prepared by a facile one-pot solvothermal method. MoS2 nanodots allow for more active sites, effective electron transfer and hole extraction for efficient HER. The electron transfer kinetics of MoS2 /CdS was firstly investigated by femtosecond transient absorption spectroscopy.